Gastroesophageal junction adenocarcinoma. A case report - Marcos Félix Osorio Pagola; Jesús Iván Gonzalez Batista; Nelia Maria Quintana Garcia (Medisur)
The case of a 68 years old patient, smoking since adolescence, with urban origins, obesity history and gastroesophageal reflux symptoms is presented. The patient was diagnosed with gastroesophageal junction adenocarcinoma type III in the Gastroenterology Department of the Provincial University Hospital of Cienfuegos where he arrived with weight loss of about 20 pounds in four months along with dyspeptic manifestations such as stomach acidity, slow digestion, bloating and epigastric pain unrelated to food consumption. No dysphagia was observed as presentation form of the disease. The patient underwent surgery and chemotherapy and has had a favourable outcome up until today. It was decided to publish this article because of the few cases of gastroesophageal junction adenocarcinoma and especially type III that are commonly presented and also because the diagnosis is, unlike this case, usually made at an advanced stage of the disease